Surface-Analytical Studies of Supported Vanadium Oxide Monolayer Catalysts - Briand, Laura Estefania (2004)
Supported vanadium oxide catalysts consisting of surface vanadia species on oxide supports were investigated by X-ray photoelectron spectroscopy  XPS and ion scattering spectroscopy ISS to elucidate the effect of calcintion temepratures as well as exposures to X-rays and He ions on the surface properties. It was found that in supported V2O5/ZrO2, V2O5/CeO2 and V2O5/Nb2O5 catalysts possessing a vanadia monolayer coverage or above, the supports are densely covered by two-dimensional surface vanadia species, and the underlaying oxide support cations are not exposed. For a supported V2O5/Al2O3 catalyst containing  however, a slight exposure of the oxide support cation Al was noted, which may originate from the much higher surface area of the support and resulting in a higher curvature of the surfaces covered by supported vanadia species.